A Comparison of Managerial Training Programs and Welfare Programs on Employee Loyalty and Productivity in Indonesian Multinational Companies - Muhammad Syafri; Teguh Setiawan Wibowo; Mohammad Gifari Sono; Siera Syailendra; Muis Muis (Westscience Press, 2026)
Employee loyalty and productivity are critical factors influencing organizational performance and long-term competitiveness, particularly in multinational companies operating in dynamic business environments. Organizations increasingly invest in managerial training programs and employee welfare programs to enhance workforce effectiveness and commitment. However, limited research has comparatively examined the relative influence of these initiatives on employee loyalty and productivity within the context of Indonesian multinational companies. This study aims to analyze and compare the effects of managerial training programs and welfare programs on employee loyalty and productivity. A quantitative research approach was employed using data collected from 175 employees working in multinational companies across Indonesia. Data were gathered through structured questionnaires measured using a five-point Likert scale and analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS 3). The findings indicate that both managerial training programs and welfare programs have positive and significant effects on employee loyalty and productivity. Managerial training programs significantly influence employee loyalty and employee productivity, while welfare programs significantly affect employee loyalty and employee productivity. The results further reveal that welfare programs exert a stronger impact on employee loyalty, whereas managerial training programs demonstrate a greater influence on employee productivity. These findings suggest that multinational companies should adopt a balanced human resource strategy that combines employee development initiatives with comprehensive welfare support to maximize organizational performance, employee commitment, and workforce effectiveness. This study contributes to the human resource management literature by providing comparative evidence regarding the effectiveness of training and welfare interventions in multinational corporate settings.